On the absolute summability of Fourier series of almost-periodic besicovitch functions - Timan, M. F.; Khasanov, Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
For almost-periodic Besicovitch functions whose spectrum has a limit point only at infinity, we establish criteria for the absolute Cesàro summability of their Fourier series of order greater than –1.